Myanmar's microfinance sector, agriculture, and COVID-19: Emerging insights and new challenges - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
This Working Paper takes comprehensive stock of the impacts of the first two waves of COVID-19 (in Q2 and Q4 2020) on the microfinance sector in Myanmar. We discuss potential impact pathways, review responses to the crisis, and present new quantitative analysis based on a set of surveys with respondents throughout the agricultural value chain. Additionally, we briefly review impacts since the military takeover on February 1, 2021. Overall, various disruptions to the microfinance sector, particularly during peak periods of COVID-19, significantly reduced overall lending from April 2020, onward. These disruptions, along with disruptions to external financing, led to greater informal borrowing, likely greater indebtedness, and lower food security. However, responses and financing accommodations to microfinance institutions (MFIs) in Q2 and Q3 2020 cushioned the sector against widespread insolvency. The events since the military takeover are creating new challenges, exacerbating the aforementioned impacts, and raising new risks of MFI insolvency and broader crises around food security, indebtedness, and poverty. Considering these findings, stakeholder recommendations underscore the importance of easing the movement of international and domestic goods. Efforts should be focused on meeting the MFIs’ need for loanable funds through mechanisms such as exchange rate hedging, credit guarantees, and loan enhancement, while continuing to encourage flexibility around existing financing. When the time comes for a full recovery, there should be a focus on facilitating additional financial injections so that MFIs can more effectively restart lending operations.